Analysis of Consumptive Behavior through Price Discount and Use of ShopeePay of PT. Jaco Nusantara Mandiri’s employees - Anthoni Salim; Irvan Rolyesh Situmorang (Sekolah Tinggi Ilmu Ekonomi Eka Prasetya, 2023)
This study aims to examine the impact of price discounts on the consumptive behavior of employees at PT. Jaco Nusantara Mandiri, as well as the influence of e-payment on their consumptive habits. This research was conducted in order to analyze how consumptive behavior among employees of PT. Jaco Nusantara Mandiri response to price discount and the use of shopeepay. The research used a descriptive quantitative method and took 102 employees of PT. Jaco Nusantara Mandiri as population. The sample size was determined using the Slovin method with a 5% error rate, resulting in 81 respondents. Data were collected using various research instruments, including direct observation, literature review, and respondent questionnaires. The data was analyzed using multiple linear regression analysis method. Three hypotheses in this study were formulated and tested using multiple linear regression analysis. The results of this study indicate the effect of price discount and e-payment have a significant influence on consumptive behavior of employees at PT. Jaco Nusantara Mandiri. Reducing reliance on price discounts and electronic payments as a transaction tool can help reduce consumptive behavior among employees of PT Jaco Nusantara Mandiri.